Empagliflozin protects against atherosclerosis progression by modulating lipid profiles and sympathetic activity - Liu, Yihai (Lipids Health Dis, 2021)
BACKGROUND: Several large clinical trials have confirmed the cardioprotective role of sodium-glucose cotransporter 2 inhibitors (SGLT2i) in patients with type 2 diabetes. However, whether empagliflozin, as an SGLT2i, could alleviate atherosclerosis progression in non-diabetic states remain unknown. METHODS: ApoE-/- mice were fed a Western diet for 12 weeks to induce atherosclerosis. On the 7th week, a group of mice were treated with drinking water containing empagliflozin (10 mg/kg/day), while another group was given normal water. At the 12th week, the whole aortas of each group were harvested. Oil Red O, HE and Movat staining were performed for atherosclerotic lesion area and size. Mouse serum lipid profiles (total cholesterol [TC], triglyceride [TG], low-density lipoprotein-c [LDL], and high-density lipoprotein-c [HDL]), systemic inflammation levels (IL-1β, IL-6 and IL-10), renin-angiotensin-aldosterone system (RAAS) components and sympathetic activity (norepinephrine and neuropeptide Y) indicators were measured by ELISA. RESULTS: Empagliflozin reduced the atherosclerotic lesion burden (-8.6 %, P = 0.004) at aortic root in ApoE-/- mice. In addition, empagliflozin decreased body weight (-3.27 g, P = 0.002), lipid profiles (TC: [-15.3 mmol/L, P = 0.011]; TG: [-2.4 mmol/L, P < 0.001]; LDL: [-2.9 mmol/L, P = 0.010]), RAAS (renin [-9.3 ng/L, P = 0.047]; aldosterone [-16.7 ng/L, P < 0.001]) and sympathetic activity (norepinephrine [-8.9 ng/L, P = 0.019]; neuropeptide Y [-8.8 ng/L, P = 0.002]). However, the anti-inflammatory effect of empagliflozin was not significantly evident. CONCLUSIONS: The early atherosclerotic lesion size was less visible in empagliflozin-treated mice. Empagliflozin could decrease lipid profiles and sympathetic activity in atherosclerosis.